2020
DOI: 10.1039/d0na00209g
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the single-atom electrocatalytic activity of transition metal-doped phosphorene

Abstract: Developing single atom catalysts (SACs) for chemical reactions of vital importance in renewable energy sector has emerged as a need of the hour. In this perspective, transition metal based SACs with monolayer phosphorous (phosphorene) as the supporting material are scrutinized for their electrocatalytic activity towards oxygen reduction reaction (ORR), oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) from first principle calculations. The detailed screening study has confirmed a breaking o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…The current densities of each system for HER process have been calculated using the following equation as proposed by Norskov et al where G *H is the free energy of the H* adsorption, T is the temperature, k B is the Boltzmann constant, and k 0 is the rate constant, which has been set to 1 because of the inaccessibility of experimental results in earlier studies for HER activity. 66,67 We also observed that the first hydrogen (*H) adsorbed at the 3-fold hollow site is thermodynamically downhill by −0.69 eV, which corresponds to the H-coverage of 0.25 ML on the Fe-NC as well as periodic surface, as it is observed in Figure S11a, b. In addition, the adsorption of the second (0.5 ML), third (0.75 ML), and fourth (1 ML) *H is further downhill thermodynamically in both cases, as other active three-fold hollow sites are also available, whereas desorbing of H 2 is always an uphill process (Figure S11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current densities of each system for HER process have been calculated using the following equation as proposed by Norskov et al where G *H is the free energy of the H* adsorption, T is the temperature, k B is the Boltzmann constant, and k 0 is the rate constant, which has been set to 1 because of the inaccessibility of experimental results in earlier studies for HER activity. 66,67 We also observed that the first hydrogen (*H) adsorbed at the 3-fold hollow site is thermodynamically downhill by −0.69 eV, which corresponds to the H-coverage of 0.25 ML on the Fe-NC as well as periodic surface, as it is observed in Figure S11a, b. In addition, the adsorption of the second (0.5 ML), third (0.75 ML), and fourth (1 ML) *H is further downhill thermodynamically in both cases, as other active three-fold hollow sites are also available, whereas desorbing of H 2 is always an uphill process (Figure S11).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a plot with exchange current density vs the Gibbs free energy of adsorption is also given in Figure b, as Δ G *H is the only activity descriptor involved in HER process. The current densities of each system for HER process have been calculated using the following equation as proposed by Norskov et al where G *H is the free energy of the H* adsorption, T is the temperature, k B is the Boltzmann constant, and k 0 is the rate constant, which has been set to 1 because of the inaccessibility of experimental results in earlier studies for HER activity. , …”
Section: Resultsmentioning
confidence: 99%
“…71,72 The scaling relations are generally studied over a set of catalyst surfaces where the reported standard relations are ∆GO=∆GOH+2 for O vs. OH and ∆GOOH=∆GOH+3.2 for OH vs. OOH intermediates (∆G denoting adsorption free energy). 73 Here, we attempt to check the plausibility of such a scaling relationship across different DFT methods for the Pt (111) surface. Previously, Norskov and co-workers have reported the sustainability of OH vs. OOH scaling relation across different functionals despite the systematic error, which was canceled by the inclusion of van der Waal's corrections.…”
Section: Orr Activity Analysismentioning
confidence: 99%
“…Coming back to Nørskov’s model, the exchange current i for H 2 evolution, a measure of the efficiency of the reaction, is plotted against the H atom adsorption free energy, Δ G H . This model, originally developed for H 2 evolution from extended metal surfaces, is commonly employed in its original formulation also for the study of SACs. The basic assumption of this model is that the adsorption free energy of the H atom is the only parameter required, as the recombination of two H atoms on the active site gives rise to the formation and desorption of H 2 into the gas phase. This hypothesis is widely verified, and in fact on metal surfaces H 2 can exist only in dissociated form or in a physisorbed state where the molecule is weakly bound to the surface by van der Waals forces .…”
Section: Introductionmentioning
confidence: 99%